Gambaran Pemimpin Ideal dalam Gurindam Dua Belas - Hermandra, Hermandra; Elmustian Elmustian; Dzakirah, Anisah (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to examine the depiction of an ideal leader as reflected in Gurindam Dua Belas (The Twelve Stanzas) by Raja Ali Haji. This research is a descriptive qualitative study using a content analysis approach on the chapters that contain leadership values. The data in this study are sourced from the text of Gurindam Dua Belas, which is analyzed to identify leadership values that describe the figure of an ideal leader. The findings show that the ideal leader in Gurindam Dua Belas is portrayed as a figure with great service and influence to the nation and significant benefit to the people they lead; possessing good morals because the leader is the head and role model for their people; being trustworthy in carrying out responsibilities and able to maintain the people’s trust; capable of deliberating (musyawarah) in decision-making so that every resulting policy considers the common interest; and able to act fairly without favoring any particular group. Thus, Gurindam Dua Belas serves not only as a literary work but also as an ethical guideline relevant to shaping leadership character to this day.